Firehawk: detecting forest fires in South Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Jake Oosthuizen describes how Firehawk, an electronic forest fire detection system, has significantly improved the early detection of fires in KwaZulu Natal´s coastal zone, thus reducing the damage to the environment and the timber industry. The sys